Eco-Friendly Behavior of Local Population, Tourists and Companies as a Factor of Sustainable Tourism Development - Sushchenko, Olena; Prokopishyna, Olena; Kozubova, Nataliia (International Journal of Engineering and Technology, 2018)
The growth of waste generation is inextricably linked with the increase in the welfare of society, so, there is a strong relationship between the dynamics of gross domestic product and waste generation. In addition to the removal of land resources, the polygons pollute the atmosphere, groundwater and soil, negatively affect the flora and fauna, and worsen the population life quality living in nearby settlements. Many nations has understanding the materiality of the lost economic benefit from the waste stream irrational management, but efficiency of measures undertaken at national and regional levels to reduce the harmful impact on the environment are reduced due to the initial orientation for secondary processing of raw materials. On the basis of the quantitative methods application, this study proves the priority of formation of the local population, tourists and business ecologically responsible behavior for environmental protection. The paper also suggests the institutional bases and economic mechanisms promoting eco-friendly behavior, that will ensure the environmental engineering innovative development.Â